2021
DOI: 10.1073/pnas.2019152118
|View full text |Cite
|
Sign up to set email alerts
|

SOX9 keeps growth plates and articular cartilage healthy by inhibiting chondrocyte dedifferentiation/osteoblastic redifferentiation

Abstract: Cartilage is essential throughout vertebrate life. It starts developing in embryos when osteochondroprogenitor cells commit to chondrogenesis, activate a pancartilaginous program to form cartilaginous skeletal primordia, and also embrace a growth-plate program to drive skeletal growth or an articular program to build permanent joint cartilage. Various forms of cartilage malformation and degeneration diseases afflict humans, but underlying mechanisms are still incompletely understood and treatment options subop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
99
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(123 citation statements)
references
References 73 publications
7
99
0
Order By: Relevance
“…3Dc), as visualized by DIC imaging (Fig. S2a-c), and is consistent with a recent report of Sox9 function in AC (Haseeb et al, 2021). Mutant tissues at 8 weeks continued to express Sox9 broadly in non-mineralized chondrocytes (Fig.…”
Section: Resultssupporting
confidence: 92%
“…3Dc), as visualized by DIC imaging (Fig. S2a-c), and is consistent with a recent report of Sox9 function in AC (Haseeb et al, 2021). Mutant tissues at 8 weeks continued to express Sox9 broadly in non-mineralized chondrocytes (Fig.…”
Section: Resultssupporting
confidence: 92%
“…However, the histological appearance of the cultures together with the twofold increased expression of Scleraxis , and the overexpression of Ccn1 ( Cyr61 ) genes, that are associated with the differentiation of progenitors in the contour of the developing cartilage, 54 indicate that chondrogenic intensification was not fully dependent of a hypertrophic progression of cartilage differentiation. Consistent with this interpretation Sox9 gene, that is believed to counteract cartilage hypertrophy in the growth plate of long bones, 55 is maintained at high expression levels.…”
Section: Discussionsupporting
confidence: 54%
“…Next, we compared the gene expression profiles of chondrocytes to all other cell type clusters (clusters 2, 5, 6, 8, 9) to identify genes enriched in healthy chondrocytes compared to other connective tissue-forming cells in the joint (Table S1, Figure S3). The master chondrocyte transcription factor Sox9 [25] and several other transcription factors (Nfatc2, Runx3, Bhlhe40, Bhlhe41, Lef1, Tsc22d1, and Sox5) showed significant enrichment in all chondrocyte clusters, suggesting that these transcription factors play major roles in regulating chondrocyte differentiation or homeostasis (Figure 1E and S3A). Previously, it has been shown that the ECM of articular cartilage is distinct from other types of connective tissues [4].…”
Section: Single-cell Profiling Reveals Cellular Heterogeneity In Healthy Murine Knee Jointsmentioning
confidence: 99%
“…Analysis of the remaining 2490 cells resulted in 10 cell clusters with distinct gene expression profiles (Figure 1B and S2A). Cell type identities were assigned based on previously published cell-type specific markers [21,[25][26][27][28][29][30][31][32][33] (Figure 1B). Cells in clusters 0, 1, 3, and 4 expressed high levels of chondrocyte markers Sox9, Col2a1, and Acan [25] and were labeled 'chondrocytes' (Figure 1C,D).…”
Section: Single-cell Profiling Reveals Cellular Heterogeneity In Healthy Murine Knee Jointsmentioning
confidence: 99%